Factors Affecting Internet Financial Reporting Disclosure to Provincial Governments In Indonesia - Ufairah Anto, Andi Sayyidatun; Kartini, Hanafi; Nirwana, Nirwana (Asian Journal of Social and Humanities, 2023)
Internet financial reporting is important because people are now geographically spread across different regions and countries. Disclosure with traditional paper-based methods has the disadvantage of limited time for filing. In the current era of globalization, Indonesian people can live in any region or country, so using internet financial reporting methods for information disclosure is available on the official government website and can be done at any time. This study aims to test or measure the impact of specific changes to existing assumptions or hypotheses, in this study are factors that affect the disclosure of internet financial reporting, where the variables used are the size of local government, regional expenditure, local original income and audit opinions on internet financial reporting in Indonesia. The type of research used in this research is quantitative research. Based on the results of research and discussion in this study, the conclusion that can be obtained based on the research variables used is that the size of local government does not affect Internet Financial Reporting which means that the size or size of local government has not been able to encourage local governments to publish financial information on local governments.